The agro-ecological suitability of Atriplex nummularia and A. halimus for biomass production in Argentine saline drylands - Falasca, Silvia Viviana (2014)
The choice of the best species to cultivate in semi-arid and arid climates is of fundamental importance, and is determined by many factors, including temperature and rainfall, soil type, water availability for irrigation and crop purposes. Soil or water salinity represents one of the major causes of crop stress. Species of the genus Atriplex are characterized by high biomass productivity, high tolerance to drought and salinity, and high efficiency in use of solar radiation and water. Based on a search of the international literature, the authors outline an agro-climatic zoning model to determine potential production areas in Argentina for Atriplex halimus and Atriplex numularia. Using the agroclimatic limits presented in this work, this model may be applied to any part of the world. When superimposed on the saline areas map, the agroclimatic map shows the suitability of agro-ecological zoning for both species for energy purposes on land unsuitable for food production. This innovative study was based on the implementation of a geographic information system that can be updated by further incorporation of complementary information, with consequent improvement of the original database.